2010
DOI: 10.1177/1087057110375615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cannabinoid Receptor 2 and Metabotropic Glutamate Receptor 1 Functional Responses Using a Cell Impedance–Based Technology

Abstract: Recently, new technologies based on biosensors and called label free have been developed. These technologies eliminate the need for using markers and dyes. The authors applied one of these technologies, based on measurement of cell impedance variation, to study the pharmacological profiles of ligands for the cannabinoid receptor 2 (CB2), a Gi-coupled receptor, and for the metabopotropic glutamate receptor 1 (mGluR1), a Gq-coupled receptor. Reference agonists and antagonists/inverse agonists for the 2 receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…In our hands, LCL densities of 50,000 cells/well were sufficient for detection of a robust GPCR response (Fig. 4), a number that is merely 2.5-fold higher than common for adherent cells (Guo et al, 2012;Scandroglio et al, 2010;Stallaert et al, 2012) and very comparable to existing suspension cell protocols described above.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our hands, LCL densities of 50,000 cells/well were sufficient for detection of a robust GPCR response (Fig. 4), a number that is merely 2.5-fold higher than common for adherent cells (Guo et al, 2012;Scandroglio et al, 2010;Stallaert et al, 2012) and very comparable to existing suspension cell protocols described above.…”
Section: Discussionmentioning
confidence: 78%
“…The initial experimental setup was based on previously published protocols for adherent cell lines (Guo et al, 2012;Scandroglio et al, 2010;Stallaert et al, 2012). While label-free assays are often deemed incompatible with suspension cells, some application examples exist for various label-free assays based on optical or impedance detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of class C GPCRs, this technique was never characterized extensively, yet it was used as a tool in two studies: Scandroglio et al [39] presented a small proof of concept study on the mGlu 1 receptor and recently we reported on the mGlu 2 receptor using the xCELLigence as a tool to assess the effect of residence time on functional efficacy of mGlu 2 PAMs [40]. Here, CHO-K1_hmGlu 2 cells stably expressing the hmGlu 2 receptor were used.…”
Section: Endogenous Glutamate Reduced Agonist Yet Enhanced Antagonistmentioning
confidence: 99%
“…Comprehensive investigation into stimulus-bias that factors in these contributing mechanisms and confounds is sorely needed. Annoura et al, 1996;Litschig et al, 1999;Scandroglio et al, 2010;Jiang et al, 2014 . mGlu 4 PAM: L-AP4 induced changes in VFT.…”
Section: Complexities Of Mglu Receptor Allosteric Modulator Pharmacologymentioning
confidence: 99%